Cross-linguistic influences in multilingual language acquisition - Gabrys-Barker, Danuta (Second Language Learning and Teaching, 2012)
This volume depicts the phenomenon of cross-linguistic influences in the specific context of multilingual language acquisition. It consists of articles on various issues relating to the syntactic and lexical development of foreign language learners from different L1 backgrounds, in many cases involving languages which are typologically distant from English, such as Russian, Croatian, Greek and Portuguese. Individual chapters highlight different areas expected to be especially transfer-prone at the level of grammatical and lexical transfer in particular contexts of language contact.